THE EVOLUTION OF THE CLASSIFICATION OF SCIENCES IN THE ISLAMIC INTELLECTUAL TRADITION - Abedi, Ahmad; Delghandi, Faezeh (Sekolah Tinggi Agama Islam Sadra, 2025)
The classification of knowledge has been a central concern in Islamic intellectual history, evolving from an Aristotelian framework to an indigenous model shaped by revelation and monotheistic epistemology. This study traces this historical development from early Muslim scholars such as Jābir ibn Ḥayyān to later figures such as Quṭb al-Dīn Shīrāzī. It highlights the shifting criteria and hierarchies of scientific classification. By using library research within a qualitative research framework and historical-philosophical approach, the study analyzes primary Arabic and Persian texts (e.g., al-Fārābī’s Iḥṣā’ al-‘Ulūm, Ibn Sīnā’s al-Shifā’) alongside secondary sources through thematic and comparative analysis to map taxonomic patterns across centuries. Key findings reveal a progression from subject-based divisions (e.g., ‘Alī’s fourfold classification) to multidimensional models integrating rational, transmitted, and mystical sciences, prioritizing interdependence over disciplinary isolation. These Islamic models offer enduring insights for interdisciplinary dialogue, modern information science, and civilizational knowledge policy, recommending future exploration of Qur’anic and hadith-based criteria to enrich global epistemology.